2017
DOI: 10.1080/20479700.2017.1298228
|View full text |Cite
|
Sign up to set email alerts
|

Staff well-being in high-risk operating room environment: Definition, facilitators, stressors, leadership, and team-working—A case-study from a large teaching hospital

Abstract: Purpose: The purpose of this case-study is to critically evaluate the relationship between healthcare staff well-being and effective team-working in high-risk operating rooms (OR) environment. Background: Evidence suggests that positive staff well-being is associated with better patient care. However, healthcare organisations are lagging behind in prioritising staff well-being. It is acknowledged that delivery of multi-disciplinary care is proportional to effective team-working. The input-process-output (IPO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
0
15
0
4
Order By: Relevance
“…It would prepare them to face the transition from past work to the OR confidently (24). Ahmed found that ORNs thought that healthcare organisations need to take an active part in ensuring the well-being of the staff, or patient care and efficient teamwork will suffer (39). Callaghan pointed out that in the dynamic nursing care of today, strength lies with specialist nurses.…”
Section: Discussionmentioning
confidence: 99%
“…It would prepare them to face the transition from past work to the OR confidently (24). Ahmed found that ORNs thought that healthcare organisations need to take an active part in ensuring the well-being of the staff, or patient care and efficient teamwork will suffer (39). Callaghan pointed out that in the dynamic nursing care of today, strength lies with specialist nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Three significant factors that can cause OR staffing shortages are: an aging population of OR nurses, little to no exposure to the perioperative clinical setting in the undergraduate nursing curriculum, and a complicated and intimidating surgical environment 6 . A case study found that the OR environment affected staff member well‐being, happiness, and job satisfaction; and a supportive and positive organizational culture, leader involvement, effective team relationships, and recognition of staff members had a direct positive influence on OR nurse retention 12 …”
Section: Overview Of the Literaturementioning
confidence: 99%
“…5(p9) In other words, well-being is an essential element of a positive practice environment. 5,6 When nurses suffer, the consequences are far reaching. A 2018 national study found a strong positive association between nurses' health and medical errors.…”
Section: Influencing Well-being In Perioperative Nursing: the Role Of Leadersmentioning
confidence: 99%
“…Unless our health care team members are functioning in a state of well‐being, it is difficult to imagine making the kind of environmental transformation that is necessary to carry us into the future. Importantly, in a case study of staff well‐being in the high‐risk OR environment, OR nurses believed that well‐being at work “underpins and drives effective team‐working and not the converse.” 5 (p9) In other words, well‐being is an essential element of a positive practice environment 5,6 …”
mentioning
confidence: 99%